Synthesis of some N-[4-(benzothiazole-2yl)phenyl]-2-aryloxyacetamide derivatives and their anticancer activities - Tay, Naime Funda; Yurttaş, Leyla; Demirayak, Şeref (Informa Healtcare, 2012)
In this study, some N-[4-(Benzothiazole-2-yl)phenyl]-2-aryloxyacetamide derivatives were prepared by reacting N-[4-(benzothiazole-2yl)phenyl]-2-chloroacetamide and different substituent phenol or thiophenol derivatives. The anticancer activities of the compounds obtained were investigated. It was observed that some of the compounds, namely 25 and 38, showed notable anticancer activity.
WOS: 000306524200007
PubMed ID: 21823837
Keywords: Benzothiazole; Antitumour; Non-small Cell Lung Cancer; Prostate Cancer